Influence of high-energy electrons irradiation on nanoceramics properties of zirconia - Aizatskyi, M.I.; Dikiy, N.P.; Dovbnya, A.N.; Fedorets, I.D.; Kushnir, V.A.; Lyashko, Yu.V.; Medvedev, D.V.; Mytrochenko, V.V.; Onishchenko, I.N.; Perezhogin, S.A.; Pelichatyi, N.M.; Danilenko, I.A.; et al. (Вопросы атомной науки и техники, 2013)
Radiation defects in nanoceramics zirconia were investigated after electron irradiation with energy 41…89 MeV up to doze 2.28…5.7·10¹⁴ electrons/cm². Radioactive isotopes ⁸⁷,⁸⁸Y, ⁸⁸,⁸⁹,⁹⁵Zr, ⁹⁵Nb, ¹⁷⁵Hf are registered after irradiation of electrons with energy 41 and 47.2 MeV. The activity of ⁸³Rb was registered after irradiation by electrons with energy 86 and 88.9 MeV. Activity of ⁸³Rb can be formed in reactions (γ, 6n) or (e, 6n). Different process of annealing radiation defects in samples of nanoceramics is detected after irradiated by electrons with energy 41…47.2 or 86…88.9 MeV. The colour centres for samples of nanoceramics after irradiated by electrons with energy 41…47.2 MeV practically completely was annealed at 500°С. For samples of nanoceramics after irradiated by electrons with energy 86…88.9 MeV and after annealing at 500°С significant absorption for lengths of waves of 430 and 470 nm is observed. It is supposed that these distinctions at annealing the colour centres of zirconia are caused by formation in nuclear reactions by high-energy electrons on isotopes of a matrix of krypton atoms. The krypton atoms are the centres segregation point defects. As a result the steady defective complexes were formed. Досліджувалися радіаційні дефекти в нанокераміці двоокису цирконію при опроміненні електронами з енергією 41…89 МеВ до дози 2,28…5,7·10¹⁴ часток/см². При опроміненні електронами з енергією 41 і 47,2 МеВ реєструються радіоактивні ізотопи ⁸⁷,⁸⁸Y, ⁸⁸,⁸⁹,⁹⁵Zr, ⁹⁵Nb, ¹⁷⁵Hf. При опроміненні електронами з енергією 86 і 88,9 МеВ додатково реєструється активність ⁸³Rb, що може бути утворена в реакціях (γ, 6n) або (e, 6n). Виявлено різний процес відпалу радіаційних дефектів у зразках нанокераміки, опромінених при енергії електронів 41…47,2 і 86…88,9 МеВ. Центри фарбування для зразків нанокераміки, опромінених електронами з енергією 41…47,2 МеВ, практично повністю відпалювались при 500 °С. Для зразків нанокераміки, опромінених електронами з енергією 86…88,9 МеВ, після відпалу при 500 °C спостерігається значне поглинання для довжин хвиль 430 і 470 нм. Передбачається, що ці розходження при відпалі центрів забарвлення двоокису цирконію обумовлені утворенням у ядерних реакціях під дією високоенергетичних електронів на ізотопах матриці атомів криптону, які є центрами сегрегації крапкових дефектів, що приводить до утворення стійких дефектних комплексів. Исследовались радиационные дефекты в нанокерамике диоксида циркония при облучении электронами с энергией 41…89 МэВ до дозы 2,28…5,7·10¹⁴ частиц/см². При облучении электронами с энергией 41 и 47,2 МэВ регистрируются радиоактивные изотопы ⁸⁷,⁸⁸Y, ⁸⁸,⁸⁹,⁹⁵Zr, ⁹⁵Nb, ¹⁷⁵Hf При облучении электронами с энергией 86 и 88,9 МэВ дополнительно регистрируется активность ⁸³Rb, которая может быть образована в реакциях (γ, 6n) или (e, 6n). Обнаружен различный процесс отжига радиационных дефектов в образцах нанокерамики, облученных при энергии электронов 41…47,2 и 86…88,9 МэВ. Центры окраски для образцов нанокерамики, облученных электронами с энергией 41…47,2 МэВ, практически полностью отожглись при 500 °С. Для образцов нанокерамики, облученных электронами с энергией 86…88,9 МэВ, после отжига при 500 °С наблюдается значительное поглощение для длин волн 430 и 470 нм. Предполагается, что эти различия при отжиге центров окраски двуокиси циркония обусловлены образованием в ядерных реакциях под действием высокоэнергетических электронов на изотопах матрицы атомов криптона, которые являются центрами сегрегации точечных дефектов, что приводит к образованию устойчивых дефектных комплексов.